Вдвоем против целого мира: [роман] / Алла Полянская - Полянская Алла (От ненависти до любви, 2015)
Экземпляры: (20160413) / Инвентарный номер: 39140 / Цена: 156.00 / Авт.знак: П 54 / ГРНТИ: 17.82.31 / ББК: 84(2Pос=Рус)6-4